Delivering happiness: a path to profits, passion, and purpose - Hsieh, Tony (New York Grand central publishing, 2010)
In this book, author shares the different lessons he has learned in business and life, from starting a worm farm to running a pizza business, through LinkExchange, Zappos, and more.
Keywords: Leadership; Success in business